1980
DOI: 10.1080/00102208008946925
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Combustion in a Reactive Environment

Abstract: The transient processes of evaporation, ignition, and combustion of a fuel droplet in a hot, reactive fuel-oxidizer environment simulating the spray interior are studied numerically, with emphasis on the relative importance of diffusional burning in the droplet vicinity and premixed burning in the ambience. It is shown that for a fuel-lean environment diffusional burning is generally possible and is initiated rapidly, whereas for a fuel-rich environment only premixed burning is possible. For a sufficiently rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 12 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…T, (11) where T, is the normal boiling point evaluated at the normal atmospheric pressure, P" and PI is the prevailing total pressure. The fuel mass fraction at the interface can be determined by (12) The oxygen mass fraction Yo, and normal velocity~,n at the interface are obtained by the conservation of species: (13) …”
Section: Conservation Of Energymentioning
confidence: 99%
See 1 more Smart Citation
“…T, (11) where T, is the normal boiling point evaluated at the normal atmospheric pressure, P" and PI is the prevailing total pressure. The fuel mass fraction at the interface can be determined by (12) The oxygen mass fraction Yo, and normal velocity~,n at the interface are obtained by the conservation of species: (13) …”
Section: Conservation Of Energymentioning
confidence: 99%
“…Botros et al [11] showed that for a fuel-lean environment, diffusional burning is generally possible and is initiated rapidly, whereas for a fuel-rich environment, only premixed burning is possible. Dwyer and Sanders [12] Downloaded by [ Rah et al [13] observed experimentally that ignition of a droplet is closely related to the formation of soot and NO z ' As the ignition delay time is large, the formation of soot is restricted.…”
Section: Introductionmentioning
confidence: 98%
“…However, experimental observations and theoretical studies 2,5,14 show that ignition occurs only a few droplet diameters away from the droplet surface. Further, the fuel vapor is almost always present in the environment prior to droplet ignition in practical sprays.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, prediction of ignition event is necessary for the simulation of spray combustion in practical energy conversion systems. Although many experimental measurements and numerical simulations of the single droplet ignition process have been carried out, [1][2][3][4][5] the ignition processes of droplets in various reactive environments remain far from well understood. Even with recent advances in computational facilities, 6 the detailed numerical simulation of individual droplet vaporization and ignition in practical spray combustion modeling is beyond the current computational capability because of the large number of droplets present in such sprays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation